(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Draga Dejanović’s poetry, next to Milica Stojadinović Srpkinja’s verses, is one of the sources of the modern Serbian female poetry. Her poetic word is rebellious, sensual, passionate, playful. She extolled the female eroticism and pleasure in her poetry and defied the patriarchal social conventions by debating erotic taboos and caricatures which were present in the folklore heritage and handwritten songbooks of the 18th and the 19th century. She anticipated modernist iconoclasm by echoing female poetic voices.